2020
DOI: 10.21203/rs.3.rs-39644/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Did the COVID-19 Pandemic Have Immediate Impacts on the Socio-Emotional and Digital Skills of Japanese Children

Abstract: Abstract Background: A novel coronavirus, SARS-CoV-2, has spread widely throughout the world. To reduce the spread of infection, children are prevented from going to school and have fewer opportunities for in-person communication. Although the pandemic has impacted the everyday lives of children, its impact on their development is unknown. This cross-sectional study compared Japanese children’s socio-emotional behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Most of these studies did not assess the SEF before the pandemic, thus preventing the ability to calculate the change in emotional problems. Those who did, for example, Moriguchi et al (2020), indeed confirmed that the pandemic imposed an immediate increase in child socioemotional difficulties.…”
Section: Transition To Kindergartenmentioning
confidence: 79%
“…Most of these studies did not assess the SEF before the pandemic, thus preventing the ability to calculate the change in emotional problems. Those who did, for example, Moriguchi et al (2020), indeed confirmed that the pandemic imposed an immediate increase in child socioemotional difficulties.…”
Section: Transition To Kindergartenmentioning
confidence: 79%